2010
DOI: 10.5194/os-6-491-2010
|View full text |Cite
|
Sign up to set email alerts
|

Long term trends in the sea surface temperature of the Black Sea

Abstract: Abstract. There is growing understanding that recent deterioration of the Black Sea ecosystem was partly due to changes in the marine physical environment. This study uses high resolution 0.25 • climatology to analyze sea surface temperature variability over the 20th century in two contrasting regions of the sea. Results show that the deep Black Sea was cooling during the first three quarters of the century and was warming in the last 15-20 years; on aggregate there was a statistically significant cooling tren… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 31 publications
5
20
0
Order By: Relevance
“…SST warming rates are not only consistent but have accelerated throughout the study period, in a context of accelerated global warming observed during this century. It is also noticeable the difference from the closer Black Sea, where Miladinova et al (2017) did not find any SST significant trend for the 1960-2015 period while Shapiro et al (2010) found a warming in the 1985-2000 period embedded in an overall downward trend for the twentieth century. Shaltout and Omstedt (2014) found a 0.51°C/decade increase for the Black Sea from 1982 to 2012 that is higher than the global 0.36°C/decade we have found in the Mediterranean for 1982-2016 but lower than the decadal trends from 1993 to 2016.…”
Section: Discussionmentioning
confidence: 88%
“…SST warming rates are not only consistent but have accelerated throughout the study period, in a context of accelerated global warming observed during this century. It is also noticeable the difference from the closer Black Sea, where Miladinova et al (2017) did not find any SST significant trend for the 1960-2015 period while Shapiro et al (2010) found a warming in the 1985-2000 period embedded in an overall downward trend for the twentieth century. Shaltout and Omstedt (2014) found a 0.51°C/decade increase for the Black Sea from 1982 to 2012 that is higher than the global 0.36°C/decade we have found in the Mediterranean for 1982-2016 but lower than the decadal trends from 1993 to 2016.…”
Section: Discussionmentioning
confidence: 88%
“…Clearly, a simple increase in the wind speed or a gradual turn in the predominant wind direction over the entire basin is not sufficient to produce such an extensive and strong pattern of variations in wave conditions. The reaction of the sea surface to changing wind conditions is generally a nonlinear process and the response in terms of the wave field not necessarily exactly follows the changes in the wind field similarly to the quite weak correlation between the temperatures of the air and surface water in the Black Sea (Shapiro et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Individual data sets are hereafter called "WOD", "ROM" and "MHI", respectively. In order to eliminate erroneous data points, the WOD + ROM data set was subject to a quality control using a two-step procedure as in Stephens et al (2002) and Shapiro et al (2010a), which is briefly outlined below. The data were subdivided geographically into 0.25 • squares.…”
Section: Geographical Compartments and Data Setsmentioning
confidence: 99%
“…For consistency with the previous study (Shapiro et al, 2010a) we calculate the monthly climate averages for the period 1910-2000 using the WOD + ROM data set. Climatic averages are calculated using the adaptive grid method as in Lozier et al (1995) and Shapiro et al (2010a) where further details can be found. The idea of this method is to use smaller grid sizes where the data is abundant and larger grids in the areas of sparse data.…”
Section: Climatology and Inter-annual Variabilitymentioning
confidence: 99%